Assessment of the economic losses caused by ovine fascioliasis and alternative interventions in tropical Africa - Ngategize, P.K.; Brokken, R.F. (Institute of Agricultural Research, 1991)
Identifies the various forms of economic loss due to ovine fascioliasis in tropical Africa; suggests a method for estimating the losses and an analytical framework for evaluating alternative management interventions; recommends that the design of biological experiments should be more comprehensive so as to generate the necessary data for economic assessment and analysis; and assesses the implications of this major constraint to increased sheep production in the Ethiopian highlands.